Geochemical processes controlling the groundwater chemistry and fluoride contamination in the Yuncheng Basin, China—An area with complex hydrogeochemical conditions - Luo, Wenting; Gao, Xubo; Zhang, Xin (PloS one, 2018)
Hydrogeochemical and stable isotope analyses and geochemical modeling were carried out to identify the major geochemical processes controlling the groundwater chemistry and fluoride contamination in the aquifers of the Yuncheng Basin, China, an area with complex hydrogeochemical conditions and severe fluoride contamination of the groundwater. The major findings of this case study include the following: 1) Cation exchange and salt effects are vital controls on the enrichment of fluoride in groundwater in the area by reducing the activity of Ca2+/F- in groundwater via ion complexation. Cation exchange increased the fluoride concentration by 2.7 mg/L when the Na/Ca molar ratio increased from 0.24 to 9.0, while the salt effect led to a ca. 5-10% increase in complex F- in groundwater due to the further dissolution of fluoride-bearing minerals in the aquifers, as suggested by a model calculation. 2) Anthropogenic contamination from pesticide and fertilizer use and industrial waste discharge is also a main source of fluoride in the groundwater. 3) Evaporation and ion effects favor the enrichment of fluoride in groundwater by encouraging the removal of Ca via precipitation. 4) The desorption of fluoride from mineral/organic matter surfaces is enhanced under alkaline conditions and a high HCO3 content in groundwater.